On the Oscillation Criteria for Fourth-Order p-Laplacian Differential Equations with Middle Term - Dandan Yang; Chuanzhi Bai (Journal of Function Spaces)
In this paper, we study the oscillatory properties of the solutions of a class of fourth-order p-Laplacian differential equations with middle term. The new oscillation criteria obtained by using the theory of comparison with first- and second-order differential equations and a refinement of the Riccati transformations. The results in this paper improve and generalize the corresponding results in the literatures. Three examples are provided to illustrate our results.